KRITIK IVAN LIIICH (DESCHOOLING SOCIETY) ANALISIS KRITIS ATAS PEMIKIRAN PENDIDIKAN IVAN LIICH DALAM DESCHOOLING SOCIETY - Yohanes Roybertus Tenja; Ermelinda Apriani Zapman (JURNAL PENDIDIKAN DAN KEGURUAN, 2026)
This article examines Ivan Illich’s critical thought on the modern education system as presented in his work Deschooling Society. Illich offers a radical critique of the dominance of schools as the primary institution of learning, which he argues has obscured the meaning of learning as a natural, social, and emancipatory process. According to Illich, institutionalized education creates individual dependence on formal certification and reproduces social inequality through claims of meritocracy. This article analyzes Illich’s view of schools as instruments of social domination that legitimize class stratification and restrict freedom in learning. Using a critical analytical approach, this paper also discusses the relevance and limitations of the deschooling society concept in the context of contemporary education. Although often considered utopian and difficult to implement comprehensively, Illich’s ideas provide an important critical reflection for promoting more humanistic, democratic, and contextual educational reforms